The sub -divisional rainfall distribution across the Western Ghats during the southwest monsoon season (MAUSAM, 1983)
The behaviour of rainfall across the entire length of the Western Ghats has been examined for the monsoon season (June to mid-September) for a period of 7 years (1970-1976). It is found that the relation between weekly mean rainfall of the meteorological sub-divisions on either side of the Ghats is one of positive correlation in the northern and central sectors and of negative correlation in the southern sector. All these three Bombay and correlations are significant at 1 % level. An explanation for the interesting change in the correlation from north to south of the Ghats is presented on the basis of synoptic analysis.